Material deprivation in the UK: beyond the binary - Nicoriciu, Ana Maria; Elliot, Mark James (International journal of population data science, 2025)
Traditional approaches to assessing poverty, which primarily rely on income levels, fail to reflect the diverse challenges experienced by those living in precarious conditions. As a result, complementary measures, such as material deprivation, have been developed. This study challenges the dichotomous categorisation of material deprivation in the UK and proposes a multi-group classification approach. The analytical sample is represented by 5,395 families (with children) in the UK. The 2019/20 Household Below Average Income dataset was selected for analysis as it represents the main source of material deprivation information in the UK. Latent Class Analysis was applied to this dataset. A combination of goodness of fit and interpretability favoured a five-class solution. Measurement equivalence was tested by comparing different family types and was confirmed, reinforcing the robustness of our results. The analysis revealed the nuanced reality and typologies of material deprivation, highlighting the complex interplay between child and adult deprivation and the prioritisation of resources.